Operational practices of lean manufacturing: Potentiating environmental improvements - Marcos José Alves Pinto Junior; Juliana Veiga Mendes (Journal of Industrial Engineering and Management (JIEM), 2017)
Purpose: The objective of this paper is to investigate how environmental improvements can be achieved through operational practices of Lean Manufacturing. Design/methodology/approach: A literature review was conducted to analyze the relationship between operational practices of Lean and reduction of environmental impact in organizational contexts. Verified theoretically, this relationship was observed in a company of the electronics industry, through an exploratory research which contemplated a mixed approach. The adopted research method consisted of a single case study, by providing greater depth and detail of the study. Utilized a research protocol, validated test pilot. The instruments for data collection were semi-structured interviews, direct observation and document analysis. The information was examined qualitatively considering the technique for content analysis. Findings: As a result of the study, it was found that there is evidence for the existence of relationship between the practices of Lean, for example, Kaizen, PDCA (plan, do, check, act), Ishikawa Diagram, Poka-Yoke, Standardized Work and Value Stream Mapping, with the reduction of environmental impacts of an organization. This reduction was observed after application of these practices that resulted in the reduction of energy consumption, water and waste generation. These results were accounted for financially, contributing to a reduction of annual costs by about US 20,900. Originality/value: The study presents in detail, the application of operational practices of Lean Manufacturing, with an effective view to reducing the environmental impact and cost reduction. The literature review, a detailed description of the application process and financial results are important information that contributes to the scientific studies that address traditional operating practices and the search for better environmental performance.
Keywords: 650; lean manufacturing; operational practices; environmental performance